2017
DOI: 10.1039/c7fd90010d
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis for Fuels: general discussion

Abstract: Nico Fischer opened a general discussion of the paper by Nora de Leeuw: You have chosen Cu as a potential catalytic material and your calculations show that Cu is not the ideal surface to decompose hydrazine to H2. Which materials would you be looking into in the future? Have you found any design parameters that should be followed? Nora de Leeuw replied: We have made in-depth studies of three diff erent mechanisms for N2H4 decomposition and these could be followed up using other potential catalysts, for exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…Thus, a high coverage might lead to an increased CO dissociation barrier. Neurock, Iglesia, and co-workers alternatively emphasized the role of H- and also H 2 O-promoted pathways for CO dissociation on the terrace surfaces that dominate nanoparticles. ,, A critique on these works mentions that the high coverage computed to be possible on a Ru 201 cluster is mainly caused by expansion and restructuring of the relatively small cluster . In addition to this, we computed the activation barrier for CO dissociation on the Co(11̅05) surface at low coverage (see the Supporting Information).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Thus, a high coverage might lead to an increased CO dissociation barrier. Neurock, Iglesia, and co-workers alternatively emphasized the role of H- and also H 2 O-promoted pathways for CO dissociation on the terrace surfaces that dominate nanoparticles. ,, A critique on these works mentions that the high coverage computed to be possible on a Ru 201 cluster is mainly caused by expansion and restructuring of the relatively small cluster . In addition to this, we computed the activation barrier for CO dissociation on the Co(11̅05) surface at low coverage (see the Supporting Information).…”
Section: Introductionmentioning
confidence: 87%
“…39,46,47 A critique on these works mentions that the high coverage computed to be possible on a Ru 201 cluster is mainly caused by expansion and restructuring of the relatively small cluster. 48 In addition to this, we computed the activation barrier for CO dissociation on the Co(11̅ 05) surface at low coverage (see the Supporting Information). The computed value of 151 kJ/mol obtained at low coverage is also high, suggesting that the particular stepedge geometry used in the work of Neurock and Iglesia is not very favorable for CO dissociation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The growing chain disrupts the CO-covered layer, making space for H-assisted CO activation (via HCOH*) without CO desorption and lowering the effective activation enthalpy and the Gibbs free energy barriers to, respectively, 127–145 and 204–220 kJ/mol, depending on the length of the growing alkylidyne chain. The very high coverage in this work (and in the work by Loveless et al) has been criticized since the high coverage in this model is probably due to the expansion and restructuring of the very small particle used in this study and likely not possible for the larger particles that are typically used in FT synthesis …”
Section: Molecular Views On the Mechanisms Of Co- And Ru-based Co-ftsmentioning
confidence: 82%
“…The very high coverage in this work (and in the work by Loveless et al 126 ) has been criticized since the high coverage in this model is probably due to the expansion and restructuring of the very small particle used in this study and likely not possible for the larger particles that are typically used in FT synthesis. 28 Su et al showed that higher CO* coverages destabilize larger molecules such as HCO* and CH x CO* more than small molecules like CH x * and CO* due to a combined effect of substrate-mediated repulsive interactions and steric hindrance. 216 Zijlstra et al investigated the influence of CO* coverage on terrace and step-edge sites on corrugated surfaces on CO activation barriers.…”
Section: Co Activationmentioning
confidence: 99%
See 1 more Smart Citation